Overlooked Fracture of the Inferior Scapular Angle Treated Conservatively - Kiyohisa Ogawa; Wataru Inokuchi; Takayuki Honma (Case Reports in Orthopedics)
Isolated fracture of the inferior scapular angle is extremely rare. We present the case of a 20-year-old female with persistent periscapular pain and a winged scapula caused by delayed union of an inferior scapular angle (ISA) fracture. Ten months previously, the patient had a car accident while seated in the left rear passenger seat. The patient visited an orthopedic clinic where a surgeon diagnosed left shoulder contusion without any abnormal radiographic findings. The left arm was kept in a sling for 2 months, as left arm elevation caused severe pain in the upper back. After sling removal, the dull pain around the left scapula continued. The patient presented at our clinic because her mother had noticed the deformity of her back. Radiographs showed a small bony fragment in the ventral side of the ISA. Computed tomography revealed a narrow gap between the ISA and the fragment. The patient’s symptoms resolved with conservative treatment that consisted of relative rest for 2 months and subsequent reinforcement exercises of the serratus anterior for 2 months.